Clinical and Bacteriological Profile of Neonatal Sepsis: A Prospective Hospital-Based Study - Jimba Jatsho; Yoriko Nishizawa; Dorji Pelzom; Ragunath Sharma (International Journal of Pediatrics)
Background. Neonatal sepsis remains one of the leading causes of mortality and morbidity in developing countries. With a dearth of data on neonatal sepsis in our country, this study was conducted to determine the incidence of clinical neonatal sepsis and evaluate the clinical, bacteriological, and antimicrobial susceptibility profile of organisms. Material and Methods. A prospective cross-sectional study was conducted in the Neonatal Unit of the National Hospital from 1st January to 31st December 2016. All neonates admitted with suspected clinical sepsis were included. Sepsis screens and cultures were sent under aseptic conditions. Data was analyzed using STATA™ version 12. Clinical features and neonatal and maternal risk factors were analyzed using chi-squared test. Bacteriological profile was analyzed with descriptive statistics. Results. During the study period, incidence of culture positive neonatal sepsis was 19 per 1000 admissions with a blood culture positivity rate of 14%. 54.5% had culture-positive early-onset sepsis (EOS). Prematurity (p=0.012), APGAR<6 (p=0.018), low birth weight (p<0.001), and maternal intrapartum antibiotics (p=0.031) significantly increased risk for culture-positive EOS. Prematurity (p<0.001), low birth weight (p=0.001), and parental nutrition (p=0.007) were significantly associated with increased risk of culture-positive late-onset sepsis. A positive screen had sensitivity of 81.8% and negative predictive value of 87.7%. Gram-negative organisms were most commonly isolated (64.6%). Coagulase-negative Staphylococci (31%) were the commonest isolate followed by Klebsiella pneumoniae (27%) and Acinetobacter (18.8%). Ninety percent of Acinetobacter were carbapenem resistant. Gram-negative sepsis had mortality of 88.9%. Conclusion. Preterm, low birth weight, low APGAR scores, intrapartum antibiotics, and parental nutrition were significantly associated with neonatal sepsis. Coagulase-negative Staphylococci, Klebsiella pneumoniae, and Acinetobacter were the principal causative organisms. Gram-negative organisms had high resistance to commonly used antibiotics.